Microstrip Filtenna with T-shaped stub Feedline for 5G Application - Ali Nyangwarimam Obadiah; Mohamad Rijal Hamid; Mohamad Kamal Abd Rahim; Noor Asniza Murad (International Journal of Integrated Engineering, 2025)
In this paper, a T-shaped stub-fed microstrip filtenna is proposed. A T-shaped stub-loaded bandpass filter is integrated with a microstrip patch antenna to form the filtenna. The selectivity of the designed filtenna is enhanced compared to the conventional microstrip patch antenna while maintaining the same bandwidth. This makes it a suitable candidate for applications requiring the same bandwidth with improved selectivity. The designs were carried out using CST Microwave Studio and validated through fabrication and measurement in the laboratory. The designed filtenna shows a rejection level improvement of 3 dB and 13 dB at the low and high frequency band edges of 3.4 GHz and 4.3 GHz, respectively. The filtenna operates at 3.6 GHz, making it suitable for 5G applications.